Kaitan Kuasa Pertambangan dengan Hak-Hak Atas Tanah dalam Undang-Undang Pokok Agraria - mukmin zakie (Jurnal Hukum IUS QUIA IUSTUM, 2000)
This paper tries to emerge the phenomena of Mining Authority and Land Right in the Basic Principle of Agrarian Law. Argumentatively the Act of Mining No. 11, 1967 does not show any relationship to the considerance of the Principal Act of Agrarian (UUPA). its existence(UUPA) is not expiicitiy stated in the Body Frame, and is mentioned unclearly on Article 2 letter b of the Basic Principle of Agrarian Law (UUPA). The Article states that land rights are rights on the land area located in certain part of the earth based on the IndonesianLaw. This perception seems dear when the Indonesian Law is indefinitely elaborated. However, if it is traced, there is a close relationship between The Basic Principal of MiningAct and the Basic Principle of Agrarian Law.